2016
DOI: 10.1007/s10545-015-9913-x
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial arterial abnormalities in patients with late onset Pompe disease (LOPD)

Abstract: These findings differ from what has been previously observed in healthy, aged-matched populations and confirm that cerebral arteries abnormalities, mainly involving the posterior circle, are not so rare in LOPD patients and are often accompanied by a lacunar encephalopathy that might represent a hypoxic-ischemic origin. A CTA or an MRA is recommended, in LOPD patients, for early detection of cerebrovascular malformations as they could lead to life-threatening events such as sub-arachnoid haemorrhage or brainst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 34 publications
1
40
0
1
Order By: Relevance
“…We demonstrated the presence of isolated unruptured intracranial aneurysms in 9.5% of patients as well as an elevated frequency (47%) of VBD . Interestingly, we also detected that 13/21 (62%) of patients presented signs of lacunar encephalopathy, not related to major risk factors . Cognitive impairment, reported in patients with infantile Pompe (IOPD), has been rarely described in LOPD.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…We demonstrated the presence of isolated unruptured intracranial aneurysms in 9.5% of patients as well as an elevated frequency (47%) of VBD . Interestingly, we also detected that 13/21 (62%) of patients presented signs of lacunar encephalopathy, not related to major risk factors . Cognitive impairment, reported in patients with infantile Pompe (IOPD), has been rarely described in LOPD.…”
Section: Introductionmentioning
confidence: 59%
“…In a previous study, we identified a cohort of patients with LOPD with variable types of cerebrovascular abnormalities . We demonstrated the presence of isolated unruptured intracranial aneurysms in 9.5% of patients as well as an elevated frequency (47%) of VBD .…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations